The Effectiveness of Giving Banana Heart to Adequate Breast Milk in Babies Less than 6 Months in Terms of Weight Gain - Fitrah Ramadani; Andi Satriana (PT Inovasi Pratama Internasional, 2022)
Breast milk (ASI) is a natural food that can be renewed, provides a complete source of nutrition for babies, protects mothers and children from disease, and has anti-inflammatory properties. One of the first steps towards a healthy and prosperous life is breastfeeding and to increase milk production, pregnant women can consume banana blossoms, which are a type of plant that contains laktagogums which have the potential to stimulate oxytocin and prolactin hormones such as alkaloids. The purpose of this study was to analyze the effectiveness of banana buds on the adequacy of breast milk in infants less than 6 months of age in terms of weight gain. The research method is a quasi-experimental research using a two group pre and post test design, with a total sample of 20 samples divided into 2 groups. The results showed that the average increase in baby weight in the experimental group before being given banana heart vegetables, the mean was 5.090 and after being given the banana flower, it increased to a mean of 5.590 with a mean difference of 0.50 while the average increase in baby weight in the control group was 4.98 increased to 5,130 with a difference of 0.15. From the results of the independent T test, it can be seen that the p value of 0.02 < 0.05 means that there is a significant difference in the average weight gain of infants in the treatment group given banana heart with the control group not given any treatment.